Kepatuhan Perawat Melaksanakan Hand Hygiene - Sahril, Wijayanti; Andi Mappanganro; Ernasari, Ernasari (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Nosocomial infections are a major problem faced by hospitals and are still quite high in Indonesia. Failure to maintain proper hand hygiene is a major cause of nosocomial infections. Nurses as a central position are very influential on the risk of spreading nosocomial infections because nurses are officers who often make direct contact with patients and must comply with hand hygiene practices. This study aims to determine the relationship between the level of knowledge, attitude, motivation, length of work and emotional intelligence on the compliance of nurses in carrying out hand hygiene in Labuang Baji Hospital. The research design used in this study was an analytical observational research design using a cross sectional approach. The determination of the sample is done by total sampling technique with a sample size of 47 people. The relationship test was carried out using the Chi-square statistical test with a significance level of < 0.05. The results showed that there was a relationship between motivation and nurse compliance in carrying out hand hygiene (ρ-value 0.036). Meanwhile knowledge with compliance (ρ-value 0.635), attitude with compliance (ρ-value 0.404), length of work with compliance (ρ-value 0.317) and emotional intelligence with compliance (ρ-value 1.000) had no relationship with nurses' compliance in carrying out hand hygiene. The conclusion of this study is that there is a relationship between motivation and nurses' compliance in carrying out hand hygiene. While the variables of knowledge, attitude, length of work and emotional intelligence have no relationship with nurses' compliance in carrying out hand hygiene at Labuang Baji Hospital. Suggestion that nurses need to be given an understanding of the importance of hand hygiene so that they carry out hand hygiene.